Overview of Pregnant Women's Knowledge About Maryam Exercises to Reduce Anxiety at the Watu Public Health Center, Barru District - Mughni Wahdaniyah S; Hartati S; Syahridayanti Syahridayanti; St. Aminah Ali (Lembaga Pengembangan Kinerja Dosen, 2026)
Maryam Exercises are a prenatal exercise method that combines movements from prayer with basic prenatal exercise techniques. These exercises aim to improve the physical, psychological, emotional, and spiritual well-being of pregnant women. Anxiety during pregnancy is common due to the long duration of pregnancy and the uncertainty of childbirth. This anxiety is often intensified by negative expectations about pregnancy and delivery, especially among primigravida women who lack maternal experience.A preliminary interview with midwives at the Watu Sub-Health Center (Pustu), Barru Regency, on June 25, 2025, revealed that 126 pregnant women had attended antenatal care since January. Midwives reported frequent complaints such as nausea, vomiting, sleep disturbances, and anxiety, with higher levels among primigravida women. These findings emphasize the need for interventions to help reduce maternal anxiety and prepare women for childbirth.This study aimed to examine pregnant women’s knowledge of Maryam Exercises as a non-pharmacological approach to reducing anxiety during pregnancy. A quantitative descriptive design was used with 30 respondents selected through quota sampling based on gestational age, pregnancy status, and frequency of antenatal visits. Data collection employed a structured questionnaire.The results showed that half of the respondents (50%, n=15) demonstrated an adequate level of knowledge about Maryam Exercises, while others showed lower or higher levels. These findings highlight the importance of expanding health education about Maryam Exercises as a strategy to reduce maternal anxiety. Integrating regular counseling and education into antenatal visits is recommended to strengthen maternal knowledge, encourage relaxation, and support physical and mental readiness for pregnancy and childbirth.